Optimizing Learning Environment in Sekolah Impian - Andi Karina Deapati; Muhammad Taufik Ishak; Yusaumi Ramadhanti; Elvita Bellani (Faculty of Engineering UNHAS, 2024)
This activity is motivated by the need to improve the quality of the learning environment at Sekolah Impian, which directly impacts student learning. Its goal is to create an optimal learning environment through good classroom design and enhancing the quality of teaching by educating teachers on child psychology. This optimization is based on the theory that the physical condition of the classroom and the quality of teaching significantly affect learning effectiveness. The activity involves all school elements, including administrators, teachers, and students, in line with community development theories that emphasize active participation. The implementation includes three stages: providing classroom design guidelines to administrators, educating teachers on child psychology, and applying these guidelines in one classroom. Participants included seven teachers and 20 students, evaluated before and after the implementation of these stages. The analytical method used involved observation and assessment of changes in teaching quality and the physical condition of the classroom. The results show that the design guidelines help administrators understand important principles in creating a good learning environment, and the psychology education helps teachers improve their teaching quality. Evaluations show improved learning environment quality and learning for kindergarten and elementary students. Active participation from all parties is crucial. The evaluation results are recommended to be used as a reference for future learning environment development.